Martensite transformations in the surface layer at grinding of parts of hardened steels - Lebedev, Vladimir; Klimenko, Natalia; Uryadnikova, Inga; Chumachenko, Tatiana; Ovcharenko, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
The mechanism of direct and inverse martensitic transformation in the surface layer of a ground part of hardened steel under the influence of the grinding temperature was investigated. It is shown that the reverse martensitic transformation is carried out during grinding according to the martensite-perlite-austenite scheme. The possibility of high-speed tempering of martensite to perlite is shown, under the action of a contact grinding temperature, which, with a further increase in temperature, turns into austenite, forming an extremely harmful defect in the working surface –quenching burn. In the present work, it is shown that the quenching burn in the form of austenite is happened by the M–P–A diffusion mechanism. This made it possible to obtain graphical and analytical dependencies, using which it is possible to calculate the Ac1 temperature points of the formation of austenite for virtually any steel grade depending on the content of carbon and alloying elements. The latter circumstance makes it possible to create such grinding conditions (the type of abrasive, the characteristics of the wheel, the use of coolant, treatment regime), at which the austenite formation temperature is not attained and the quenching does not happen. Thus, as a result of the studies, it is possible to determine safe grinding temperatures for steels of different chemical compositions and treatment regimens that do not cause an increase in the grinding temperature above a certain level.